INJURIES AND FATALITIES RESULTING FROM THE 2005 SOUTH ASIA EARTHQUAKE. A HOSPITAL EXPERIENCE: South Asia Earthquake – A Hospital Experience - Sheikh, Irfan Ali; Shah, Shahzad Saleem; Iftikhar, Afshan; Bashir, Riaz Anwar (Pakistan Armed Forces Medical Journal, 2006)
Background: The South Asia quake struck South Asia with its epicentre in Pakistan on 8th October 2005, originating from a previously recognized fault line but of unsuspecting magnitude of death and destruction. The Earthquake measured 7.6 on the Richter scale and caused massive loss of life and extensive damage to property never seen before in the history of Pakistan.Methods: Earthquake related admissions and deaths to one of the two major tertiary care hospitals receiving casualties from the quake zone from 8th October 2005 through 1st November 2005 were analysed. All medical data from the hospital records was reviewed for quake related injuries and information about pattern of injuries received and treatment administered.Results: A total of 3128 earthquake related admissions were recorded in the hospital with 39 in-hospital deaths. Admission rates were approximately 2:1 by gender, males affected more.Conclusion: Earthquake related injuries are varied and multifactorial. Comprehensive surveillance and a well developed plan for all Medicare setups need to be in place and when actively rehearsed, can help lead to better management preparedness.